Dental associations with blood mercury in pregnant women. Issue 3 (21st December 2015) - Golding, Jean; Steer, Colin D.; Gregory, Steven; Lowery, Tony; Hibbeln, Joseph R.; Taylor, Caroline M.
Abstract: Objectives: There is curiosity concerning the source of mercury that is absorbed into the mother's blood and which may affect the developing fetus. This study therefore sets out to determine the extent to which dental amalgam (DA) may contribute to total blood mercury (TBHg) levels of pregnant women in the UK. Methods: Whole blood samples and information on diet and socio‐demographic factors were collected from pregnant women ( n  = 4484) enrolled in the Avon Longitudinal Study of Parents and Children (ALSPAC). The whole blood samples were assayed for total mercury levels using inductively coupled plasma dynamic reaction cell mass spectrometry (ICP‐DRC‐MS), and the women were retrospectively asked about features of their dental care during the pregnancy. Linear regression was used to estimate the relative contributions of DA to TBHg levels (log‐transformed) based on R 2 values, compared to the results from dietary and socio‐demographic variables. Results: The contribution to the variance of the mothers' TBHg levels by dental variables was 6.47%, a figure comparable to the 8.75% shown for seafood consumption in this population. Dietary and dental variables explained 20.16% of the variance, with socio‐demographic variables contributing only a further 3.40%. The number of amalgams in the mouth at the start of pregnancy accounted for most of the variance in dental variables. Conclusions: Dental amalgam contributes a comparable amount of variance in TBHg to seafood consumption in this population. However, because the measures of DA exposure were imprecise, these findings are likely to be an underestimate. There is no evidence to date in the literature that fetal exposures to mercury from maternal DAs have adverse effects on the developing child, but long‐term studies are warranted.